Legal Certainty of an Electronic Deed Made by A Notary - Moh Ali; Anisa Solekha (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Technology and information that are increasingly advanced and growing rapidly during the industrial revolution 4.0 and society 5.0 today can affect the performance of Notaries. One of them is the idea of implementing a cyber notary, especially an electronic notary deed that can be a solution for Notaries to be able to carry out their duties accurately, quickly, and up-to-date. Opportunities for implementing a cyber notary are contained in the general explanation of Article 15 paragraph (3) of the UUJN regarding cyber notaries, as well as the opportunity to conduct teleconferences/ videoconferences contained in Article 77 of the Company Law. Paragraph (4) letter b, so it must remain in the form of the original notarial deed in the form of paper and not in electronic form. In addition, the general explanation of the UUJN is also different from its body which requires making an appearance or meeting directly with a notary, reading the deed before the parties, keeping the deed secret from other parties who are not interested, etc. So it is necessary to have a uniform legal basis or provide a legal umbrella so that a cyber notary in the form of an electronic deed can be carried out by a notary. The purpose of the research is to find out and find the concept of future arrangements related to the making of an electronic notary deed in order to better guarantee legal certainty and legal protection for the community. The research method used is normative juridical or descriptive literature law research. The results of the research are that Indonesia must implement technological developments and IT systems related to cyber notaries to be able to carry out their duties and authorities, change the substance of articles that hinder the implementation of cyber notaries, delete article 5 paragraph 4 letter b. So that cyber notaries related to electronic deeds can be implemented and have legal certainty and protection.